CELEBRITY ENDORSERS VS EXPERT ENDORSERS: WHO CAN AFFECT CONSUMER PURCHASE INTENTION FOR HALAL FASHION PRODUCT? - Yan Putra Timur; Ririn Tri Ratnasari; Nailul Author (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
This study aims to analyze the effect of using two types of endorsers, namely celebrities and expert endorsers, on consumer purchase intentions between halal fashion products. The method used in this study is PLS-SEM for model evaluation. This study analyzes the effect of using two types of endorsers, namely celebrities and expert endorsers, on consumers' purchase intentions between halal fashion products. The method used in this study is PLS-SEM for model evaluation. This study gave respondents a full-color print advertisement containing a photo of artist April Jasmine as a celebrity endorser and expert fashion designer Hannie Hananto as an expert endorser. We use celebrity and expert endorsers as independent variables and consumer purchase intention in halal mode as the dependent variable. The result showed that celebrity endorsers positively influence consumer purchase intention in halal fashion products. Meanwhile, expert endorser does not affect consumer purchase intention on halal fashion products. The results of this study reveal that celebrity endorsers positively affect consumers' purchase intentions for halal fashion products. However, marketers must pay attention to the suitability of selecting the type and attributes of the endorser with the product they support. The goal is that the marketing costs incurred by the company in the endorser use strategy are more effective and follow marketing objectives.